Biocompatible fluorescent polyamine‐based cyclophosphazene hybrid nanospheres for targeted cell imaging. (13th November 2019) - Akram, Raheel; Arshad, Anila; Dar, Sami Ullah; Basharat, Majid; Liu, Wei; Zhang, Shuangkun; Wu, Zhanpeng; Wu, Dezhen
Abstract : Fluorescent nanoprobes are highly desirable toolkit for bioimaging applications. This study reports the first example for the synthesis of a nontoxic prototypical fluorescent organic compound 2‐benzo[ d ]thiazol‐2‐yl)‐3‐(2‐chloro‐4‐(dimethylamino)phenyl)acrylonitrile (BCA) and its entrapment into the poly[cyclotriphosphazene‐co‐polyethyleneimine] cross‐linked (PCPEI) nanospheres named as BCA@PCPEI for targeted cell imaging application. The as‐prepared BCA@PCPEI nanospheres were thoroughly characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), fourier transform infrared (FTIR), thermogravimetric analysis (TGA), and phosphorus‐31 nuclear magnetic resonance ( 31 P‐NMR) analyses. The surface functional analysis of the nanospheres was performed by X‐ray photoelectron spectroscopy (XPS), which proves that the content ratios of elements belong to the precursors concentrations. The as‐prepared nanospheres displayed emission at 606 nm with bright orange fluorescence at any concentration. Moreover, the nanospheres were also less cytotoxic and maintained remarkable cell viability up to 100 μg/mL. Owing to the fluorescence with higher emission, this material has shown excellent cell imaging performance with better targeting ability to HeLa cells.